The Effect of STEM-Based Physics Learning and Local Wisdom of Bengkulu on Students’ Critical Thinking Skills in the Concept of Particle Dynamics - Yulensi Klareza; Irwan Koto; Fitri April Yanti (FKIP - Universitas Riau, 2026)
Physics teaching practices in schools generally still focus on low-level thinking through routine exercises, so critical thinking skills as a 21st-century competency are not being maximised. This research attempts to look into the impact of STEM-based physics learning integrated with traditional Bengkulu games affect pupils' ability to think critically about particle dynamics. The research employed a nonequivalent control group and a quasi-experimental design. A total of 66 Grade XI students served as research subjects: 33 in the experimental class and 33 in the control class, 28 Grade XII students participated in the critical thinking test trial, and three expert validators (lecturers and physics teachers) were involved. The research instruments were an essay test and Facione’s Critical Thinking Skills Assessment Rubric. The data were analysed using non-parametric inferential tests and descriptive statistics (Mann-Whitney U). The findings demonstrated that Grade XI students' critical thinking abilities were significantly impacted by STEM-based physics instruction combined with Bengkulu local knowledge, with Sig< 0.001 and an effect size of 0.54 (High). It was concluded that STEM-based physics Learning combined with Bengkulu traditional knowledge was successful in enhancing critical thinking abilities in the idea of particle dynamics.